Efficacy of high-intensity versus continuous training on serum lipids, fat mass and lean mass in adults with metabolic syndrome: a post hoc analysis of a clinical trial (2022)
ABSTRACT: Background: Exercise is a strategy known to improve the lipid and inflammatory profile of the metabolic syndrome (MS). However, experimental evidence about which exercise intensity is most beneficial on lipids and body composition in patients with MS is scarce and contradictory. We compared the effect of high-intensity (HIIT) versus continuous (MICT) aerobic training on serum lipids, fat mass and lean mass in patients with MS. Methods: We carried out a secondary analysis of a controlled, randomized, clinical trial in adults of both sexes with MS, who underwent a supervised, three-times/week, 12-week treadmill program. HIIT (n=29) consisted of six intervals with one-minute, high-intensity phases at 90% of peak oxygen consumption (VO2peak) for a total of 22 minutes. MICT (n=31) trained at 60% of VO2peak for 36 min. Lipid profile (High-density lipoprotein [HDL-C], Low-density lipoprotein [LDL-C] and Triglycerides [TGL]) was determined by enzymatic methods, TC (Total cholesterol) was calculated using the Friedewald formula, free fatty acids (FFA) were measured by gas chromatography, fat mass and lean mass was assessed by dual-energy X-ray absorptiometry (DXA). An analysis of covariance was conducted, and effect sizes estimated. Results: Subjects had a median (interquartile range, IQR) age of 51.5 years (46.0-56.0), and body mass index of 27.9 kg/m2 (27.9-32.8). Compared to MICT, HIIT was not superior at reducing LDL-C, TGL, TC, TC/HDL (Total cholesterol to HDL ratio), Palmitic acid and Stearic acid or at increasing HDL-C and Linoleic acid. Compared to baseline values, LDL-C, HDL-C, TC, TC/HDL, TGL and FFA levels remained unaltered in both groups. HIIT was not superior to MICT in improving body composition. HIIT decreased visceral adipose tissue (VAT) (25.48 gr [95% CI -12.30 to 63.26]) with an effect size of -0.68 and increased lean mass index (LMI) 0.26 kg [95% CI 0.00 to 0.52] with an effect size of 1.41. MICT reduced android to gynoid fat mass ratio (A/G FM) with an effect size of -0.73. Both interventions reduced body fat percentage (FM%), body fat mass index (FMI), and appendicular fat mass index (AFMI) and increased appendicular lean mass index (ALMI) and skeletal muscle mass index (SMI). Conclusions: Compared to MICT, HIIT was not superior at reducing serum lipids, saturated FFA or increasing polyunsaturated FFA. Both training types reduced fat mass and improved lean mass. Keywords: Metabolic syndrome; High-intensity interval training; Moderate continuous training, Free fatty acids, Lipids, Body composition.